Marketing Analysis of Red Onion (Allium ascalonicum linn) in Tanpabulu Village, Poleang Utara Subdistrict, Bombana Regency - Fifi, Fifi; Ine Fausayana; Weka Gusmiarty Abdullah (International journal of technology and education research, 2024)
This study aims to determine the marketing channel of shallots in Tampabulu Village, North Poleang Subdistrict, Bombana Regency and to determine the margin and efficiency of shallot marketing in Tampabulu Village, North Poleang Subdistrict, Bombana Regency. The population in this study were 45 farmers, collector traders, retailers, and unknown consumers. The sampling technique for farmers is census sampling so that the number of samples is the same as the population of 45 people. The sampling technique for collectors, retailers and consumers is snowbal sampling. Data analysis used is descriptive analysis, marketing margins and marketing efficiency. The results showed that (1) shallot marketing channels in Tampabulu Village, North Poleang Subdistrict, Bombana Regency, there are 3 channels, namely channel I is farmers - retailers - consumers, channel II is farmers - intermediary traders - retailers - consumers, channel III is farmers - intermediary traders - consumers. (2) The marketing margin of shallot farmers in Tampabulu Village, North Poleang Subdistrict, Bombana Regency in each channel has a difference where the largest margin value is in channels I, II and IV, namely IDR 7,000 and the lowest is in channel III with a margin value of IDR 4,000. The difference in marketing margins is due to the fact that the type III channel is not from farmers and consumers, while the type I, II and IV marketing channels are from farmers and consumers. The greater the difference between the purchase price and the selling price, the greater the marketing margin. Conversely, the smaller the difference between the selling price and the purchase price, the smaller the marketing margin. While the value of shallot marketing efficiency in channel I is EP = 1.49% with efficient category. Channel II is EP = 8.98 and in marketing channel III is EP = 4.82%. From the results of the analysis of the efficiency of the four channels is efficient, because it is smaller than the value of marketing efficiency (EP < 33%)